Enrichment of guinea pig (Cavia porcellus) meat with omega-3 fatty acids by diets with fish oil and sacha inchi (Plukenetia volubilis) seeds - Guevara V., Jorge (2016)
The aim of this study was to enrich guinea pig (Cavia porcellus) meat with omega3 polyunsaturated fatty acids by diets with omega-3 sources. A total of 48 male guinea pigs, 42 day old and 615 g body weight were used. The guinea pigs were randomly assigned to four treatments with three replicates (pens) with four individuals each. The dietary treatments were: 1) Control diet; 2) 1.0% fish oil supplemented diet; 3) 4.0% sacha inchi seeds (Plukenetia volubilis) supplemented diet; and 4) 1.0% fish oil + 4.0% sacha inchi seeds supplemented diet. The experiment lasted 28 days. The meat of guinea pig supplemented with fish oil contained 1.36% large chain omega-3 fatty acids (0.63% eicosapentaenoic acid [EPA] + 0.73% docosahexaenoic acid [DHA]) and those supplemented with the fish oil + sacha inchi had 0.99% large chain omega-3 fatty acids (0.44% EPA + 0.55% DHA). Guinea pigs on the control diet and those supplemented with sacha inchi seeds contained no large chain omega-3 fatty acids (EPA/DHA) but short chain omega-3 fatty acid α-linolenic acid (ALA). Furthermore, meat of guinea pig fed on the sacha inchi diet showed the highest level of polyunsaturated fatty acids (51.35%), the lowest content of monounsaturated fatty acids (21.97%) and the lowest concentration of saturated fatty acids (25.49%). It is concluded that the diet with fish oil produced retention of omega-3 EPA and DHA in guinea pig meat, while the diet with sacha inchi seeds only retained omega-3 ALA.